Diagnóstico da aplicação dos princípios da construção enxuta em empresas construtoras - Richter, Vitor (2014)
This study aims to conduct a diagnosis of the current situation of two construction companies based on the principles of lean construction. To do so, first, was characterized by lean production literature review; with an emphasis on lean production in construction applications, "lean construction philosophy" later a case study was conducted in both companies, with site visits. The tool adopted for the extraction of information was the use of a structured questionnaire. Since the questionnaire was based on the 11 principles proposed by Koskela (1992). For each principle questions that link the use of the principle observed in company with the different points of views that make up the value chain of construction (engineering, management, workers, customers, suppliers and designers) have been prepared. With this technique it was possible to identify the strengths and weaknesses in relation in relation to the principles of lean construction.